Profil Diferensiasi Leukosit dan Biomarker Stress Sapi Perah Laktasi dengan Pemberian Feed Supplement di Kelompok Ternak Tunas Mekar KSU Tandangsari - Fazriyati, Mia Nuriyah; Mushawwir, Andi; Tanuwiria, Ujang Hidayat (Universitas Islam Negeri Alauddin Makassar, 2023)
This research was conducted from April to June 2023 at the Tunas Mekar Cattle Group, KSU Tandangsari. As many as 16 Friesian Holstein (FH) dairy cows lactating 1-5, were used in this study to review the leukocyte differentiation and biomarker stress profiles and find out which treatment had the best effect on the leukocyte differentiation profile and biomarker stress. The study used a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments included P0 (control) consisting of 60% forage + 40% concentrate; P1 = 60% forage + 40% concentrate (97% concentrate + 3% protein by-pass); P2 = 60% forage + 40% concentrate (95% concentrate + 3% protein by-pass + 2% Ca-PUFA); and P3 = 60% forage + 40% concentrate (93% concentrate + 3% protein by-pass + 2% Ca-PUFA + 2% organic minerals). Based on the results of the study, it was shown that feeding supplementation had a significant effect (P<0.05) on the leukocyte differentiation profile and stress biomarkers of lactating dairy cattle in the Mekar Tunas Livestock Group, KSU Tandangsari. Lactation dairy cows treated with P3 = 60% forage + 40% concentrate (93% concentrate + 3% protein by-pass + 2% Ca-PUFA + 2% organic minerals) had lower mean leukocyte differentiation and biomarker stress than controls ( P<0.05). This can be interpreted that the provision of rations supplemented with feed supplements in the form of 3% protein by-pass + 2% Ca-PUFA + 2% organic minerals is able to reduce the level of heat stress as seen based on leukocyte levels and their differentiation and stress marker enzymes in the blood.